(untitled) (Economic and Political Thought, 2018)
Based on the monograph by Ivo van de Wijdeven, Visegrád’s ghosts: Unknown history of Poland, Hungary, the Czech Republic and Slovakia [j. nid. De spoken van Visegrád, De onbekende geschiedenis van Polen, Hongarije, Tsjechië en Slowakije], published in the Netherlands in April 2018 and the materials from the international conference “Place and role of the Visegrád Group states in the European Union” at Lazarski University, the author attempts to look at the issues from the point of view of a foreign reader and the Visegrád Group states’ diplomats, the conference participants. The diplomats demonstrated official optimism and determination, and they urged that a forum like the Visegrád Group is necessary, and they decidedly refuted a hypothesis that it is a competitive structure with the European Union. The scientists, more critical in nature, drew attention to the differences between the V4 states in order to illustrate the threats resulting from interest clashes, e.g. particular states’ attitudes to Russia. Everybody agreed that the V4 states face a great test, i.e. joint protection of the shape of the coherence policy and the best possible distribution of resources in the future budget. The author of the first monograph devoted to the V4 states written in Dutch, in its conclusions, presents the opinion that the future of Europe, both the European Union and the Visegrád Four, depends on the answer to the question whether the Member States are able to translate their different interests into their common strength instead of common weakness.